Biography of resistance : the epic battle between people and pathogens - Zaman, Muhammad H. (Muhammad Hamid) (Harper Wave, an imprint of HarperCollinsPublishers, 2020)
"Superbugs, born of antibiotic resistance, are a growing global health crisis. Award-winning educator and researcher at Boston University Muhammad Zaman, Ph. D. tells the story about how we got here and what we must do to combat this threat that connects us all"--